2021
DOI: 10.3389/fmicb.2021.638326
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Microbial Activity, Bacterial Community Composition and Function in a Long-Term Continuous Soybean Cropping System After Corn Insertion and Fertilization

Abstract: Corn-soybean rotation and fertilization are common practices improving soil fertility and crop yield. Their effects on bacterial community have been extensively studied, yet, few comprehensive studies about the microbial activity, bacterial community and functional groups in a long-term continuous soybean cropping system after corn insertion and fertilization. The effects of corn insertions (Sm: no corn insertion, CS: 3 cycles of corn-soybean rotations and CCS: 2 cycles of corn-corn-soybean rotations) with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 64 publications
3
13
0
Order By: Relevance
“…In the present study, although fertilization had no effect on the alpha diversity of bacteria ( Figure 1 ), significant differences were revealed in bacterial community structure among the different treatments ( p < 0.01, Figure S2 ). Acidobacteria and Proteobacteria were two of the most abundant phyla observed in the bacterial community, as shown in previous studies [ 77 , 78 ]. Both of them can properly enhance soil fertility and sustainability when they were enriched in soil [ 60 ].…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, although fertilization had no effect on the alpha diversity of bacteria ( Figure 1 ), significant differences were revealed in bacterial community structure among the different treatments ( p < 0.01, Figure S2 ). Acidobacteria and Proteobacteria were two of the most abundant phyla observed in the bacterial community, as shown in previous studies [ 77 , 78 ]. Both of them can properly enhance soil fertility and sustainability when they were enriched in soil [ 60 ].…”
Section: Discussionsupporting
confidence: 77%
“…Shao et al found that the AP and AK contents increased significantly with increasing continuous cropping of peanuts [ 53 ]. It was reported that the overuse of inorganic fertilizer significantly decreased soil pH [ 54 ], which was confirmed in our study. Soil pH is a key factor affecting soil bacterial diversity and community composition; soil pH affects soil microbial physiological metabolism, alters the competitive relationship within microbial communities, and inhibits the growth of unadapted microbes [ 10 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Microorganisms in the phyla Proteobacteria and Acidobacteria usually accounted for most of the soil bacterial communities ( Fierer et al, 2007 ; Rao et al, 2021 ). Among the soil bacteria, Proteobacteria , Acidobacteriota , Actinobacteria , Bacteroidota , Gemmatimonadetes were the dominant phyla, and L14 showed significantly higher relative abundance of soil beneficial bacteria ( Proteobacteria , Bacteroidota , Acidobacteriota , Verrucomicrobiota ) than L10.…”
Section: Discussionmentioning
confidence: 99%